Exposure to nitrous oxide in a paediatric dental unit - FIONA GILCHRIST, C. JOHN WHITTERS, ALISON MARION CAIRNS, MATTHEW SIMPSON & (IAPD and Blackwell, 2007)
The aim of this study was to evaluate the 8-h time-weighted average (8-h TWA) exposure to nitrous oxide of dentists working in a paediatric dental unit, and to relate this to various operator, patient and environmental factors.